2022
DOI: 10.1177/00220345221082918
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Effect on Caries of Sugars Intake: Ten-Year Update

Abstract: An update of the systematic review of evidence on the association between amount of sugars intake and dental caries, as well as on the effect of restricting sugars intake to <10% and <5% energy (E) on caries, was conducted, almost 10 y since the review that informed the World Health Organization (WHO) Guideline on Sugars. The aim was to systematically review epidemiological data published from 2011 to 2020 on the amount of sugars consumption and levels of caries and to report the findings for adults and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…On one hand, both childhood obesity and dental caries are more frequent among poorer families [ 2 , 10 ]. On the other hand, sugar intake is an established behavioural determinant of both obesity and caries in childhood and adulthood [ 11 , 12 ]. The reviews also identified large heterogeneity between the primary studies.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, both childhood obesity and dental caries are more frequent among poorer families [ 2 , 10 ]. On the other hand, sugar intake is an established behavioural determinant of both obesity and caries in childhood and adulthood [ 11 , 12 ]. The reviews also identified large heterogeneity between the primary studies.…”
Section: Introductionmentioning
confidence: 99%
“…22 Several systematic reviews have recently been updated and published in dentistry encompassing a wide range of topics that shed light and impact clinical practices. [23][24][25][26] Even the Cochrane collaboration supports the updating of systematic reviews and provides guidelines for updating. 21 This updated systematic review provides promising data to the clinician to utilize pterygoid implants as a favorable alternative to sinus floor augmentation or zygomatic implants, both of which are more invasive, expensive, and may risk compromising sinus health.…”
Section: Discussionmentioning
confidence: 99%
“…Updating systematic reviews is generally more efficient than starting all over again when new evidence emerges 22 . Several systematic reviews have recently been updated and published in dentistry encompassing a wide range of topics that shed light and impact clinical practices 23–26 . Even the Cochrane collaboration supports the updating of systematic reviews and provides guidelines for updating 21 …”
Section: Discussionmentioning
confidence: 99%
“…In the development of public sugar reduction strategies and intake guidelines, oral diseases have played a role because of the causal and well-researched relationship between sugar intake and dental caries (Moores et al, 2022;Moynihan, 2016;World Health Organization, 2015). However, the literature behind these recommendations does not mention periodontal diseases such as gingival inflammation (Moores et al, 2022;Moynihan, 2016). This lack of mention of periodontal diseases in WHO publications deserves scrutiny, as there are some studies providing evidence that sugar consumption is also associated with gingival inflammation and dental plaque formation.…”
Section: Introductionmentioning
confidence: 99%